1997
DOI: 10.1023/a:1008202723066
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer: Pretreatment drug resistance parameters (GSH-system, ATase, P-glycoprotein) in tumor tissue and their correlation with clinical and prognostic characteristics

Abstract: We conclude that 'high' levels of DRP in tumor tissue of breast cancer patients are part of the initial phenotype of the malignant cells. Due to its high prevalence (83% in EBC, 100% in primarily metastatic breast cancer), PGP did not add to prognostic information. High levels of GSH, GST and GPx were associated with favorable clinical characteristics and good prognosis, whereas low levels of GSH and GST activity were associated with more aggressive or more advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 23 publications
3
26
0
1
Order By: Relevance
“…However, very limited data are available in the literature in this field and the precise mechanism of action, the relationship between multidrug resistance genes, and their clinical impact on the outcome of patients with breast cancer remain unclear, as published results have been discordant (Keith et al, 1990;Buser et al, 1997;Frassoldati et al, 1997;Silvestrini et al, 1997;Trock et al, 1997;Ferrero et al, 2000;Leonessa and Clarke, 2003). Few data are available concerning the impact of multidrug resistance genes on the clinical outcome of patients treated for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, very limited data are available in the literature in this field and the precise mechanism of action, the relationship between multidrug resistance genes, and their clinical impact on the outcome of patients with breast cancer remain unclear, as published results have been discordant (Keith et al, 1990;Buser et al, 1997;Frassoldati et al, 1997;Silvestrini et al, 1997;Trock et al, 1997;Ferrero et al, 2000;Leonessa and Clarke, 2003). Few data are available concerning the impact of multidrug resistance genes on the clinical outcome of patients treated for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MRP1 can act as a transporter of glutathione conjugates (Muller et al, 1994). Although the precise role of the glutathione detoxification pathway in the MDR phenomenon has not yet been fully elucidated, the isoenzymes of the glutathione-S-transferase (GSTs), namely the subclass GSTpi (EC 2.5.1.18), have been extensively reported to be overexpressed in tumour cells displaying the MDR phenotype (Keith et al, 1990;Buser et al, 1997;Ferrandina et al, 1997;Frassoldati et al, 1997;Silvestrini et al, 1997;Boku et al, 1998;Stoehlmacher et al, 2002;Oudard et al, 2002;Cullen et al, 2003;Galimberti et al, 2003;Bennaceur-Griscelli et al, 2004). However, the role of GSTs proteins remains controversial in the literature.…”
mentioning
confidence: 99%
“…However, to date the results are still somewhat controversial and may vary from population to population. (Gilbert et al, 1993;Silvestrini et al, 1997;Buser et al, 1997;Helzlsouer et al, 1998;Millikan et al, 2000;Mitrunen et al, 2001;Gudmundsdottir et al, 2001;Huang et al, 2003;Egan et al, 2004;Sreenath et al, 2005;Moureau-Zabotto et al, 2006;Unlu et al, 2008;Saxena et al, 2009;Arun et al, 2010;Pongtheerat et al, 2011;Zhang et al, 2011;Ramalhinho et al, 2011;Aguiar et al, 2012;Ramalhinho et al, 2012;Saxena et al, 2013;Khabaz, 2014;Rodríguez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies revealed GSTP1 polymorphism has no correlation with clinical and pathologic tumor characteristics (Buser et al, 1997;Huang et al, 2003) only a few studies showed an inverse correlation with ER (Gilbert et al, 1993;Silvestrini et al, 1997;Moureau-Zabotto et al, 2006). Furthermore, two studies of Pongtheerat and colleagues reported that GSTP1 polymorphism was unrelated to increased risk of breast cancer, but found an inverse relationship between GSTP1 genotype and progesterone receptor protein (Pongtheerat et al, 2009;Pongtheerat et al, 2011), and positive correlation with better tumor differentiation and grade (Cairns et al, 1992;Haas et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation